HOW POSITIVE IS POSITIVE PSYCHOTHERAPY? (EXAMINATION OF POSITIVE PSYCHOTHERAPY) - ÖZEN, YENER; TÜRKMEN, İREM (Innovare Journal of Social Sciences, 2023)
The aim of this study is to discuss positive psychotherapy in general terms and concepts. Positive psychotherapy is an important psychotherapy approach founded in 1968 by Nossrat Peseschkian. Since the 1990s, it has become more known. It is a combination of psychodynamic, existential, cultural, and behavioral theories. The word positive here means the actual, the real. The psychotherapist helps the client to see and understand the problem by making the current symptom more understandable. Positive psychotherapy also has a positive view of people. He argues that people are inherently good and should focus on the good aspects they have. It has three main principles: Hope, balance, and counseling. Positive psychotherapy is based on the balance model. By interpreting the symptoms positively, it is aimed for the client to approach the balance. It tries to explain the symptoms with its primary and secondary abilities. It aims to strengthen the positive resources of individuals to cope with the conflicts they experience, to continue their lives in a better quality and to realize themselves.